Embolized Guidewire into Central Aorta: A Nightmare in the Pediatric Intensive Care Unit - Nath, R.K.; Agrawal, Richa; Sarowa, Manoj; Pandit, Neeraj (Journal of Pediatric Intensive Care, 2018)
A 4-month-old preterm, critically ill infant weighing 3.8 kg was admitted to our pediatric intensive care unit with congestive cardiac failure due to a large ventricular septal defect and its sequelae. During an attempt to insert a central line into the right subclavian vein at bedside, the guidewire inadvertently entered the subclavian artery and embolized distally. After multiple failed retrieval attempts, including surgical femoral cut-down to retrieve the wire, it was removed finally by fluoroscopic-guided percutaneous catheterization with the help of a cardiac bioptome and a gooseneck snare utilizing a novel maneuver.
Keywords: guidewire; pediatric; retrieval